STRATEGI KOMUNIKASI PARIWISATA OLEH DINAS PARIWISATA SUMATERA BARAT DALAM MENINGKATKAN BRAND IMAGE OBJEK WISATA DI SUMATERA BARAT: Strategi komunikasi pariwisata - Defhany defhany defhany; Ria Edlina; Dion Eriend (Commed : Jurnal Komunikasi dan Media, 2020)
This study discusses the Tourism Communication Strategy by the West Sumatra Tourism Office in Improving the Brand Image of Tourism Objects in West Sumatra. The purpose of this research is to describe the things that become supporters and obstacles in the implementation of the tourism communication strategy by the West Sumatra Tourism Office in Increasing the Brand Image of Tourism Objects in West Sumatra. This is because there are still at least domestic tourists or foreign tourists visiting existing tourist objects. in West Sumatra, considering that many tourist objects in West Sumatra are not inferior to other provinces, this research can encourage the West Sumatra Tourism Office to improve the quality of tourist objects in the West Sumatera area. The research method used in this research is descriptive qualitative research conducted in 2019. The informants in this study consisted of 3 employees at the West Sumatra Tourism Office, namely Head of Marketing and Brand Strategies, head of Division Human Resources Development and Business Protection, and the Tourism Resources Development Section of the West Sumatra Provincial Tourism Office. Informants are determined by purposive sampling. The results of this study are, West Sumatra tourism communication strategy by promoting tourism using various social media such as Instagram and Facebook and optimizing the use of the West Sumatra Tourism Office website and through marketing and promotion of the advantages of tourism objects by involving various parties, such as the tourist business actors, investors, journalists from various media and visiting tourists. Always maintaining various interconnected tourism products, starting from cultural festival events, transportation to tourist objects, up-to-date information about tourist objects, tourism activities accompanied by promotions in various cities and the availability of communication media that are easy to find by tourists and a friendly communication culture with tourists visiting the tourist attraction.